LACTIC ACID BACTERIA OF WESTERN ALGERIA. I: CHARACTERISTICS OF STRAINS ISOLATED FROM RAW MILK AND OLIVE OIL (Sciences & Technologie. C, Biotechnologies, 2003)
A total of 154 strains of Lactococcus, Lactobacillus, Enterococcus and Streptococcus were isolated from olive oil samples or from cow’s, goat’s and sheep’s raw milk samples collected in West of Algeria. The lactic acid bacteria strains were phenotypically identified and characterized using microbiological and biochemical tests. Of the 119 isolates of Lactococcus, 50 strains were identified as Lc. lactis subsp. lactis, 34 strains were identified as Lc. lactis subsp. biovar. diacetylactis and 35 strains were identified as Lc. lactis subsp. cremoris, but with difference in carbohydrate fermentation patterns. 21 strains were identified as Lactobacillus sp., 11 strains were identified as Enterococcus faecium and 03 strains were identified as Streptococcus thermophilus.